Goldenhar Syndrome: Craniofacial implications with emphasis on the temporomandibular joint and therapeutic approaches (Research, Society and Development, 2025)
Goldenhar Syndrome (GS) is a spectrum of malformations that primarily affects structures derived from the first and second branchial arches, resulting in alterations of the mandible, maxilla, and ears, and may be associated with ocular and vertebral anomalies. The condition is generally characterized by unilateral craniofacial involvement, with the temporomandibular joint (TMJ) being one of the most relevant manifestations, impacting orofacial functions such as mastication, swallowing, phonation, and facial aesthetics. The objective of this study was to analyze, through a narrative literature review, the craniofacial alterations associated with GS, with emphasis on the TMJ, in addition to discussing therapeutic approaches and the role of the dentist in functional and aesthetic rehabilitation. A bibliographic survey was conducted in the PubMed and LILACS databases, initially with 50 articles published between 2015 and 2025, of which 29 met the inclusion criteria and were analyzed regarding anatomical manifestations, classifications, and therapeutic possibilities. Patients with SG may present with anything from condylar hypoplasia to absence of the temporomandibular joint (TMJ), as well as alterations in the glenoid fossa and articular disc, resulting in facial asymmetry, malocclusion, and functional limitations. The Pruzansky-Kaban and OMENS+ classification systems assist in defining the severity of the deformity and in individualized therapeutic planning. Treatment options include functional orthopedics, bone grafts, distraction osteogenesis, and alloplastic prostheses, generally in a multidisciplinary approach. In conclusion, SG significantly compromises the TMJ, requiring early and continuous monitoring, with the dentist's role being fundamental in recognizing structural alterations and in appropriate therapeutic planning.